Prevalence and determinants of multiple chronic conditions (MCC) among young adults in Indian households: an analysis of NFHS-5 - Geetanjali Takale; Avantika Handore; Angeline Jeyakumar; Swapnil Godbharle (BMC, 2024)
Abstract Background Multiple chronic conditions (MCC) are defined as the presence of two or more chronic conditions, that significantly impact health status, functional capacity, quality of life, and overall healthcare management. Despite the significant evidence on chronic disease burden, the co-existence of MCC within a household in low- and middle-income countries (LMICs) is less studied. This study therefore estimates the prevalence of MCC and its determinants among adults in the Indian households. Methods Data used in this study were drawn from the fifth round of the National Family Health Survey (NFHS) conducted in 2019-21. Data sets of men (15-54 years) and women (15-49 years) were used for the study. The total sample size of adults for this analysis was N = 239,848. The outcome variable of this study was multiple chronic conditions (MCC) in adults which included a total of nine chronic conditions (hypertension, diabetes, chronic respiratory diseases, chronic kidney disorders, cancer, thyroid disorders, obesity, and heart diseases, consuming alcohol, chewing tobacco, and smoking) documented in NFHS-5. Descriptive statistics and binary logistic regression analysis were used to quantify the results. Results A prevalence of 5.5% of MCC in adults emerged from our study. Logistic regression analysis identified that younger age, males (AOR 0.36 (0.33-0.39)), urban areas (AOR 1.11 (1.02-1.17)) as the place of residence, and participants representing SC (AOR 0.89 (0.81-0.97)), and ST (AOR 1.30 (1.17-1.45)), had a higher risk of MCC irrespective of level of education, type of occupation, marital status, or wealth index, and states from any category of social progress. Conclusion A 5% prevalence of MCC specifically obesity, substance use, and hypertension calls for integrated efforts aiming at behavior change, and regulatory efforts to prevent further increase of MCC among young adults in India.